Trends in pneumonia mortality among US adults, 1999 to 2023 - Nawei Song; Juan He; Xianghua Shuai; Hana Zhu; Keran Xia (Medicine, 2026)
Influenza combined with pneumonia creates a persistent public health burden across the United States, continuously threatening adult survival and consuming massive medical resources. This population-based epidemiological research aims to map long-term mortality shifting patterns linked to flu and pneumonia among American adults spanning the 25-year window from 1999 to 2023. Our analytical data were extracted from the Centers for Disease Control and Prevention WONDER public mortality repository. Deaths triggered primarily by influenza or pneumonia were screened through International Classification of Diseases, 10th Revision diagnostic codes J09 to J18. Two core mortality indicators, crude rates and age-standardized mortality rates, were computed for the whole population and separate subgroups. Joinpoint regression modeling was adopted to quantify yearly percentage shifts (annual percent change) and average annual changing magnitudes (average annual percent change), paired with 95% confidence intervals (CIs) to judge statistical significance. Stratified subgroup comparisons were completed across demographic and geographic dimensions, with statistical significance defined as P < .05. Across the full research timeframe, the national age-adjusted mortality rate for influenza and pneumonia dropped substantially, falling from 35.93 per 100,000 residents in 1999 to 16.46 per 100,000 residents in 2023, with an average annual decline of 3.18% (95% CI = −3.53 to −2.83, P < .05). Mortality burdens consistently ran higher in male populations relative to females. Among all racial subgroups, non-Hispanic Black adults bore the heaviest baseline mortality pressure in 1999 (38.66 per 100,000 population) and also saw the most marked relative reduction by 2023 (19.01 per 100,000 population). Rural counties maintained elevated age-adjusted mortality values compared with metropolitan regions in all survey years. Adults aged 85 and above exhibited the highest crude death rate, peaking at 751.78 per 100,000 people in 1999. Notably, the 55 to 64 middle-aged group was the only stratum with a statistically meaningful upward trend in crude mortality, with an average annual percent change of 0.78% (95% CI = 0.20–1.37, P < .05). This study demonstrates long-term declining trends in US influenza and pneumonia-related mortality with persistent disparities by sex, age, race/ethnicity, and urban–rural status.